E-Business Online Experience, Satisfaction and Trust: Basis for Customer Loyalty among Selected SMEs in Bulacan - Allan B Pleno; Araceli M Reclusado (Research Synergy Foundation, 2024)
This research paper investigates the relationship between e-business online experience, satisfaction, and trust as predictors of customer loyalty among small and medium enterprises (SMEs) in a selected area of Bulacan. Considering the increasing reliance on digital platforms for e-commerce, issues surrounding online security and user privacy have arisen, raising concerns about consumer trust in e-business environments. Employing a quantitative research methodology, the study utilizes a quantitative descriptive and correlational design to measure and identify the mean and standard deviation of online experience, satisfaction, and trust as independent variables, with customer loyalty as the dependent variable. The findings reveal that SMEs in Bulacan have a strongly positive perception of their e-business online experience, particularly highlighting the simplicity, visual appeal, and effectiveness of the websites they use. They appreciate the quality of information provided by these e-business platforms, which facilitates e-purchases through up-to-date content and straightforward transactions. The study also indicates a strong agreement among SMEs regarding the effectiveness of e-business websites in meeting consumer expectations for repeat purchases, while also identifying areas for improvement in online performance features. Moreover, SMEs generally perceive a high level of security regarding e-business platforms, particularly regarding information transmission and electronic payment safety. However, there was a slightly lower perception of user privacy concerns. The regression analysis indicates that both e-business online experience and customer satisfaction are significant predictors of customer loyalty, underscoring the importance of enhancing these aspects to cultivate lasting customer relationships.